2014
DOI: 10.1016/j.semcdb.2013.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell dynamics in the hair follicle niche

Abstract: Hair follicles are skin appendages of the mammalian skin that have the ability to periodically and stereotypically regenerate in order to continuously produce new hair over our lifetime. The ability of the hair follicle to regenerate is due to the presence of stem cells that along with other cell populations and non-cellular components, including molecular signals and extracellular material, make up a niche microenvironment. Mounting evidence suggests that the niche is critical for regulating stem cell behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
150
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(150 citation statements)
references
References 132 publications
0
150
0
Order By: Relevance
“…Otherwise dormant stem cells residing in the bulge region sporadically enter into the cell cycle in response to signals derived from the base of the niche, and give rise to progeny that repopulate the hair follicle. Alongside putative stem cell markers such as keratin 15 and the transcription factor Sox9, which are expressed throughout the bulge region, other markers are expressed heterogeneously, such as the hematopoietic progenitor cell antigen CD34, which is expressed more strongly in the distal region while Lgr5 is enriched proximally (Rompolas and Greco, 2014) (Fig. 4B).…”
Section: Hair Follicle Cyclingmentioning
confidence: 99%
“…Otherwise dormant stem cells residing in the bulge region sporadically enter into the cell cycle in response to signals derived from the base of the niche, and give rise to progeny that repopulate the hair follicle. Alongside putative stem cell markers such as keratin 15 and the transcription factor Sox9, which are expressed throughout the bulge region, other markers are expressed heterogeneously, such as the hematopoietic progenitor cell antigen CD34, which is expressed more strongly in the distal region while Lgr5 is enriched proximally (Rompolas and Greco, 2014) (Fig. 4B).…”
Section: Hair Follicle Cyclingmentioning
confidence: 99%
“…The skin organ is a consummate model for studying selforganization processes because of its accessibility to experimentation, its relatively flat configuration, and the availability of genetic tools in mice (13)(14)(15). Previous studies have shown that a Significance This study opens avenues to improve the ability of adult skin cells to form a fully functional skin, with clinical applications.…”
mentioning
confidence: 98%
“…In contrast, the matrix cells still surround the DP and thus maintain contact. This is important because signals from the DP stimulate the matrix cells to continuously proliferate and to finally expand as a column upward, differentiate, and generate the concentric layers of the IRS and the HS (reviewed in Rompolas and Greco 2014). Each cell lineage induces the expression of distinct keratins.…”
Section: Hf Sc Dynamicsmentioning
confidence: 99%
“…However, the understanding how the niche elements work together and how they interact with macroenvironmental and environmental factors to initiate and promote a new HC and thus to regenerate a new HF is still not complete. Signaling pathways that regulate SC quiescence, proliferation, and differentiation include Wnt, BMP, Notch, and FGF18 (reviewed in Rompolas and Greco 2014). It has been demonstrated in various studies that various signals from these pathways constantly compete, and it is a delicate balance of these signals that keeps SCs and their progenies either in a stage of rest or in a stage of proliferation.…”
Section: Hc Controlmentioning
confidence: 99%
See 1 more Smart Citation